Information technology challenges and opportunities - Forbes, David; Wongthongtham, Pornpit; Terblanche, C.; Pakdeetrakulwong, U. (2018)
In the last decade, the world of data and digital enterprise has expanded, becoming greatly enriched but also more complex as research and development activity continues to introduce new opportunities and challenges across the spectrum of human educational endeavour.